Judeans and Jews : four faces of dichotomy in ancient Jewish history - Schwartz, Daniel R. (Kenneth Michael Tanenbaum series in Jewish studies., 2014)
Presenting the Second Temple era as an age of transition between a territorial past and an exilic and religious future, Judeans and Jews sharpens our understanding of this important era.